Antibody-based detection of lysine modification of hepatic protein in mice treated with retrorsine. (20th October 2020) - Cheng, Ting; Li, Weiwei; Yang, Xiaojing; Wang, Huali; Zhang, Fan; Li, Na; Lin, Ge; Zheng, Jiang
Abstract: Many pyrrolizidine alkaloids (PAs), an important class of natural products, are hepatotoxic and carcinogenic. Increased attention has been paid to PA poisoning cases worldwide. Generally, most PAs themselves are not toxic. However, reactive intermediates formed from PAs by metabolic oxidation have been linked to toxicity and carcinogenesis. PAs themselves are generally not toxic, and their reactive metabolites resulting from metabolic oxidation are considered to be an essential responsible for PA toxicities. Protein modification by the electrophilic metabolites is proposed to play a key role in PA-induced cytotoxicity. The present study investigated the interaction of lysine residues of proteins with reactive metabolites of toxic PAs. Antibodies selectively recognizing lysine-based protein adduction were prepared and characterized. ELISA and immunoblot methods, in the presence and absence of synthetic model PA adducts, were used to test specific binding of the antibodies to modified lysine residues of BSA and to hepatic proteins extracted from mice treated with retrorsine. The lysine residue adduction was also detected in the tissues of retrorsine-treated mice by use of an immunohistochemical approach. In conclusion, the prepared antibodies selectively recognized the lysine adducts and may be used for the investigation of mechanisms of toxic action of PAs.